It's great to suck at something : the unexpected joy of wiping out and what it can teach us about patience, resilience, and the stuff that really matters - Rinaldi, Karen (Atria Books, 2019)
What if the secret to resilience and joy is the one thing we<U+2019>ve been taught to avoid? When was the last time you tried something new? Something that won<U+2019>t make you more productive, make you more money, or check anything off your to-do list? Something you<U+2019>re really, really bad at, but that brought you joy? Odds are, not recently. As a sh*tty surfer and all-around-imperfect human Karen Rinaldi explains in this eye-opening book, we live in a time of aspirational psychoses. We humblebrag about how hard we work and we prioritize productivity over play. Even kids don<U+2019>t play for the sake of playing anymore: they<U+2019>re building blocks to build the ideal college application. But we<U+2019>re all being had. We<U+2019>re told to be the best or nothing at all. We<U+2019>re trapped in an epic and farcical quest for perfection. We judge others on stuff we can<U+2019>t even begin to master, and it<U+2019>s all making us more anxious and depressed than ever. Worse, we<U+2019>re not improving on what really matters. This book provides the antidote. (It<U+2019>s Great to) Suck at Something reveals that the key to a richer, more fulfilling life is finding something to suck at. Drawing on her personal experience sucking at surfing (a sport she<U+2019>s dedicated nearly two decades of her life to doing without ever coming close to getting good at it) along with philosophy, literature, and the latest science, Rinaldi explores sucking as a lost art we must reclaim for our health and our sanity and helps us find the way to our own riotous suck-ability. She draws from sources as diverse as Anthony Bourdain and surfing luminary Jaimal Yogis, Thich Nhat Hanh, and Jean-Paul Sartre, among many others, and explains the marvelous things that happen to our mammalian brains when we try something new, all to discover what she<U+2019>s learned firsthand: it is great to suck at something. Sucking at something rewires our brain in positive ways, helps us cultivate grit, and inspires us to find joy in the process, without obsessing about the destination. Ultimately, it gives you freedom: the freedom to suck without caring is revelatory.